Pencarian Rute Terpendek untuk Pemetaan UMKM di Kecamatan Negeri Katon Menggunakan Algoritma A-Star - Yulmaini, Yulmaini Yulmaini; Berlian, Agnes Tria (Politeknik Harapan Bersama, 2025)
In the regional economy, micro, small and medium enterprises (MSMEs) have a very significant role in driving economic growth and opening up employment opportunities for the community. However, the lack of information regarding business locations and optimal routes for MSMEs is still an obstacle in improving accessibility. The lack of information regarding the fastest route to the location of MSMEs leads to limited accessibility, especially for people who are unfamiliar with the area. Therefore, a more optimal strategy is needed to determine the best way to improve the distribution efficiency and mobility of MSMEs. The purpose of this research is to use the A-Star algorithm for mapping MSMEs to find the fastest route to the location of MSMEs. This research explicitly combines MSME spatial data with the implementation of the A-Star algorithm for route optimization. The results show that the A-Star algorithm is able to effectively speed up the route search process by taking into account the appropriate heuristic value. With the implementation of this algorithm, accessibility to MSMEs locations is significantly improved, allowing customers and businesses to easily find MSME locations with greater cost and time efficiency. Implementation of the A-Star algorithm in increase in MSME accessibility through optimal route efficiency.